Heterogeneous Polyoxometalates: Efficient, Facile and Reusable Catalysts for One-Pot Synthesis of Dihydropyrimidinones - FAZAELI, RAZIEH; TANGESTANINEJAD, SHAHRAM; ALIYAN, HAMID (Asian Journal of Chemistry, 2010)
Polyoxometalates (POMs) used as efficient catalysts for the threecomponent condensation reaction of an aldehyde, with β-ketoester and urea in acetonitrile to afford the dihydropyrimidinones. Compared to the classical Biginelli reaction conditions, the present method consistently has the advantage of excellent yields and short reaction times. Furthermore, the catalyst could be easily recovered after completion of the reaction and reused without a considerable change in its activity.